Percy Jackson and the lightening thief - Riordan, Rick (UK Puffin books Penguin random house, 2013)
After learning that he is the son of a mortal woman and Poseidon, god of the sea, twelve-year-old Percy is sent to a summer camp for demigods like himself, and joins his new friends on a quest to prevent a war between the gods